All Questions Topic List
None Questions
Previous in All Question Next in All Question
Previous in None Next in None
Question Number 143326 by SOMEDAVONG last updated on 13/Jun/21
L=limn→+∝(23−1)(33−1)(43−1)...(n3−1)(23+1)(33+1)(43+1)...(n3+1)
Answered by gsk2684 last updated on 13/Jun/21
n3−1n3+1=(n−1n+1).(n2+n+1n2−n+1)L=limn→∞(13.24.35.46...n−2n−1.n−1n+1)(73.137.2113.3121...n2+n+1n2−n+1)=limn→∞(1.2n−1.n+1)(n2+n+13)=23limn→∞n2+n+1n2−1=23
Terms of Service
Privacy Policy
Contact: info@tinkutara.com